Novel Agents for the Treatment of Pancreatic Adenocarcinoma: Any Light at the End of the Tunnel? - Dimou, Anastasios T; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Pancreatic cancer is a disease with dismal prognosis and treatment options are limited. Development of novel active compounds is mandatory. A number of pancreatic cancer clinical trials that included a novel agent among their arms were presented at the recent 2010 American Society of Clinical Oncology (ASCO) Annual Meeting. It appears that IGF-1R inhibition might be effective and this should be tested in further trials. Microtubule stabilization with ixabepilone in combination with EGFR does not lead to promising improvement in prognosis whereas nab-paclitaxel in combination with anti-angiogenetic agents is a combination not previously tested that showed an acceptable safety profile. This combination might be worth testing in a phase II clinical trial. Last but not least, CTLA-4 blockade has an acceptable toxicity profile but its efficacy needs to be proven over placebo in phase II and III trials. Finally, understanding of the tumor biology and biomarker analysis from the clinical trials is warranted. Image: Yale University School of Medicine. New Haven, CT, USA.